A severe monkeypox infection in a patient with an advanced HIV infection treated with tecovirimat: clinical and virological outcome. (December 2022) - Viguier, Clément; de Kermel, Tristan; Boumaza, Xavier; Benmedjahed, Nina Sicard; Izopet, Jacques; Pasquier, Christophe; Delobel, Pierre; Mansuy, Jean-Michel; Martin-Blondel, Guillaume
Highlights: Severe and protracted monkeypox virus infection can occur in a patient with AIDS. In this setting, tecovirimat might improve symptoms and decrease viral replication. Randomized controlled trials in humans are underway. Patients who are diagnosed with monkeypox should be routinely tested for HIV. Abstract: A patient aged 28 years who is immunocompromised and living with HIV/AIDS became infected with the monkeypox virus (MPXV). His clinical condition deteriorated for 37 days, with fever, skin lesions, and diarrhea before going to the infectious diseases department, where his severe, protracted infection was treated with tecovirimat for 14 days. His condition rapidly improved, and the skin lesions decreased, as did the MPXV loads, with no adverse events. This case indicates that tecovirimat might be effective for treating patients who are immunocompromised and are infected with MPXV.